Identification of Geothermal Potential Based on Fault Fracture Density (FFD), Geological Mapping and Geochemical Analysis, Case Study : Bantarkawung, Brebes, Central Java - ., Oktoberiman; Ramadhan P, Dimas Aji; W, Fajar Rizki; A, Rizal Tawakal (KnE Energy, 2015)
Insufficient of conventional energy production today in Indonesia, encouraging all elements to discover an alternative energy. Geothermal is one of big potential alternative energy in Indonesia regarding the conditon of geological setting in Indonesia which has 129 active volcanoes. Bantarkawung is located in the western of Mount Slamet where hot spring occured as geothermal manifestation. This indicate geothermal potential in that area. This research is aimed to identify geothermal potential that lies in bantarkawung using Fault Fracture Density (FFD), Geological Mapping and Geochemical analysis. Based on FFD analysis known that anomaly area is located at central and northeast of research area, and based on geological mapping known that area composed by mudstone unit and sandstone unit, water temperature of research area is 43 °C to 62 °C, by using geochemical analysis of major ions HCO3-,Cl-,S042- known that the type of hot water is bicarbonate water which characterized as an outflow zone of geothermal system. Keywords: Bantarkawung; FFD; geochemichal analysis; geothermal; hot springs